Go West Young Mensch! The Rise and Decline of the Jewish Community of Carbon County, Wyoming (U.S.A.) (Global Journal of Human-Social Science, 2019)
Abstract not found
Keywords: wyoming; carbon county; jewish community; jewish history; identity